Monopoli Dalam Perspektif Islam - Satria kemal gustia; Muhammad hafizh ramdhani; Sri oktaviani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Monopoly is a commonly used market mechanism in developing countries. The practice of monopoly harms small businesses and provides a great opportunity to gain as much profit as possible. The approach is library research or literature study. This literature research method collects the necessary information by reading relevant sources. To synthesize and present the data found, it is necessary to collect information and data from various sources such as articles, magazines, and books. The results show that, given the values of Islamic economics, monopolies that harm society and cause inequality are considered to deviate from the basic principles of Islamic economics. The realization of an economic system that is in line with Islamic teachings requires efforts to prevent and overcome monopoly. To overcome these problems, various efforts are needed, including encouraging healthy market competition, avoiding monopolistic behavior, maintaining Islamic economic values, and increasing public awareness about the negative impact of monopoly from an Islamic economic perspective.